Effect of Aquaculture Wastewater And Zarrouk in Increasing Biomass, Protein, and Carotenoids levels of Spirulina platensis - Anisa Millah Taqiyyah; Yenny Risjani; Asep Awaludin Prihanto; Uun Yanuhar; Mohammad Fadjar (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research S. platensis has been analyzed for its productivity. Analysis of the productivity of S. platensis on the use of fish culture wastewater media. S. platensis production can be increased by aquaculture wastewater. Aquaculture wastewater enhances the production of cell density, SGR, biomass, protein, and carotenoid of S. platensis. Abstract Increased productivity of Spirulina sp. in the form of high protein, carotenoids, and biomass content can be achieved by improving its nutrient supply. Inorganic fertilizers are nutrient sources, which are generally used in the culture of this organism on laboratory and industrial scale, but there are several drawbacks, including their high costs and limited availability. Several studies have also reported the use of zarrouk fertilizer as a standard culture medium for Spirulina platensis. Therefore, this study aims to determine the effect and the best concentration of fish culture wastewater treatment in Spirulina platensis culture using biomass, protein content, and carotenoid pigments as indicators. A two-factorial completely randomized designs (CRD) was used in this study, where the factors include the dose of organic waste and Zarrouk fertilizer. The microalgae samples, namely S. platensis were cultured using fresh water. This research consists of two factors. The first factor is the dose of organic waste, and the second factor is the dose of Zarrouk fertilizer. The wastewater treatment consisted of 0, 2, 4, and 6 ml/L, while Zarrouk dosages include 0, 0.5, and 1 ml/L. The best results were obtained from the sample treated with 6 ml/L aquaculture wastewater without the addition of Zarrouk. Furthermore, this treatment gave biomass production of 0.781 g/L, 50.441% protein, and 1.246 mg/L carotenoids. Based on the results, S. platensis culture can be carried out using fish culture wastewater without the addition of Zarrouk fertilizer.